Analysis of land use type pattern and light rail transit (LRT) ridership - Malayandy, Sathiya Vaani (2016)
Rail ridership particularly relies on several factors which affect the ridership. One of the factors is the land use, the distribution of different land use categories in and near rail transit station areas can have measurable impacts on transit ridership. More study proves that the land use characteristics are strong determinants of transit ridership. Hence, this paper studies the relationship between rail station ridership and land uses. This study examines the land use distribution around 400 metres radius area of Light Rail Transit (LRT) station in Ampang Line. The LRT stations of Ampang Line under the Dewan Bandaraya Kuala Lumpur (DBKL) territory were selected and MapInfo, Geographical Information System software (GIS) was used to analyse the land use area within the 400 metres radius of LRT stations. From the study, it can be concluded that the land use pattern of distribution of the station are mainly comprises of residential uses. Second largest land uses is commercial and followed by the institutional uses. The land uses of recreational and open space are available in minimum areas. Three stations namely, Sentul Timur, Bandar Tun Razak and Miharja LRT stations with various land use pattern were selected to analyses the relationship of the land use and passenger ridership. Bandar Tun Razak LRT station with 62% of residential uses and Miharja LRT station with the highest commercial uses triggers more ridership than the other station. It shows that the ridership is much higher in the stations where great amount of residential and commercial land use is around. Both land uses can contribute to trip production and attraction for the station ridership.